Ca(II)‐Mediated Regioselective One‐pot Sequential Annulation of Acyclic compounds to Polycyclic Fluorenopyrans. Issue 22 (11th October 2018) - Yaragorla, Srinivasarao; Rajesh, P.; Pareek, Abhishek; Kumar, Ankit
Abstract: Herein we report a facile synthesis of tetracyclic fluorenopyrans from simple acyclic reactants, propargyl alcohols and 3‐methylpentane‐2, 4‐dione under calcium catalysis. This one‐pot, 3‐component reaction proceeds through a sequential allene formation, Friedel‐Crafts cyclization/cycloisomerization, intramolecular aldol reaction, Claisen rearrangement, and 6‐ endo dig cyclization to result in the formation of fluorenopyrans (indeno[2, 1‐g]chromenes). This strategy was further used in the synthesis of 3‐iodo‐fluorenopyrans, by adding iodocyclization to the above sequence of reactions (4‐CR). Noticeably, this highly practical, atom and the step‐economic procedure is catalyzed by a sustainable (alkaline earth) metal salt and tolerates the broad substrate scope, allowing the further transformations and synthetic utilities of these complex polycyclic moieties. Abstract :